Dynamic crosstalk between HSCs and liver microenvironment: multicellular interactions in the regulation of liver fibrosis - Wang, Luping; Huang, Yi; Chen, Jingrong; Gao, Jialu; Chen, Sihan; Zhao, Mingqi; Lin, Jiguo; Zhou, Shunqing; Shen, Yannan; Cheng, Yunyun (Frontiers in Cell and Developmental Biology, 2025)
Liver fibrosis is induced by persistent stimulation of various factors, resulting from complex multicellular interactions and multifactorial networks. Without intervention, it can progress to cirrhosis and even liver cancer. Current understanding suggests that liver fibrosis is reversible, making it crucial to explore effective therapeutic strategies for its alleviation. Although the activation and proliferation of hepatic stellate cells (HSCs) play a pivotal role in liver fibrosis, the importance of hepatocytes, cholangiocytes, liver sinusoidal endothelial cells (LSECs) and immune cells cannot be ignored, the interactions of these cells with HSCs are worth discussing. Therefore, based on the diversity of cell composition in the liver organ, this review summarizes the impact of the parenchymal and nonparenchymal hepatic cells on liver fibrosis, including hepatocytes, cholangiocytes, hepatic macrophages, T cells, NK cells, B cells and LSECs, as well as the fibroblast subpopulations. And further discussed the interactions of these cells with HSCs and illustrated intercellular signal transduction among these cells in contributing to liver fibrosis. Clarifying the roles and interactions of various cells in the development of liver fibrosis will be helpful to explore effective strategies for the treatment of liver fibrosis.